The fracturing of work and employment relations. (2nd January 2019) - Dundon, Tony
ABSTRACT: This article presents an argument that work and employment relationships are increasingly 'fractured' and 'fragmented'. The argument first reviews the changing contexts of investor-capitalism (financialisation), which shows that a market ontology and an excessive individualistic ideology is pervasive in employment regulation. The expansion of financialised capitalism is then related to contemporary employment practices about 'pay inequality' and 'talent' selection. These serve to eschew collective structures of collaboration and fragment labour standards. The result is a series 'protective gaps' about worker voice, legal regulation, technology and labour control. A number of challenges and opportunities for the way the subject area is taught and researched in mainstream business schools are outlined.